2015
DOI: 10.1126/sciadv.1500606
|View full text |Cite
|
Sign up to set email alerts
|

Memristive phase switching in two-dimensional 1T-TaS 2 crystals

Abstract: Electrical switching to multiple novel metastable states in a correlated two-dimensional crystal.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
287
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(309 citation statements)
references
References 35 publications
13
287
1
1
Order By: Relevance
“…To demonstrate the pure electron doping effect on CDW, more direct doping experiments by negative perpendicular electric field or liquid-gated method should perform. Some works reported the suppression of CCDW by in-plane electric field [22][23][24][25][26]. By measuring the temperature dependence of resistivity (R − T ), Yoshida et al found the in-plane field cannot affect the NCCDW/ICCDW transition in R − T curve, but can introduce a metastable state with very low resistivity at low temperatures [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the pure electron doping effect on CDW, more direct doping experiments by negative perpendicular electric field or liquid-gated method should perform. Some works reported the suppression of CCDW by in-plane electric field [22][23][24][25][26]. By measuring the temperature dependence of resistivity (R − T ), Yoshida et al found the in-plane field cannot affect the NCCDW/ICCDW transition in R − T curve, but can introduce a metastable state with very low resistivity at low temperatures [24].…”
Section: Resultsmentioning
confidence: 99%
“…Some works reported the suppression of CCDW by in-plane electric field [22][23][24][25][26]. By measuring the temperature dependence of resistivity (R − T ), Yoshida et al found the in-plane field cannot affect the NCCDW/ICCDW transition in R − T curve, but can introduce a metastable state with very low resistivity at low temperatures [24]. If we consider that the R − T in CCDW, NCCDW, and ICCDW reflects the related structural characteristics, one can infer that the in-plane field induced the metastable state with different structural characteristics, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated the suppression of CDW phase transitions using polar electrolytes, as well as resistive switching between the different phases. As the material approaches the 2D limit, however, significant changes have been observed in the transport properties (4,5,8). However, the microscopic nature of the 2D state remains unclear.…”
mentioning
confidence: 99%
“…19,20 In addition, electrostatic gating has been reported to exhibit some control over the transition temperatures. 21 While these CDW transitions are largely electronic rather than structural, their existence, and manipulation in layered materials suggests there may also be other materials and mechanisms for nonvolatility in very thin materials.…”
Section: Introductionmentioning
confidence: 99%